Analysis Of Mover School Curriculum Implementation On Learner Motivation - Putu Yulia Angga Dewi; Kadek Hengki Primayana (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
This study aims to analyze the implementation of the driving school curriculum on learner motivation. Education always undergoes changes, developments, and improvements in accordance with developments in life. Changes and improvements in the field of education include several components in the implementation of education, namely: teacher competence, quality of education, curriculum, facilities and infrastructure as well as changes in innovative learning strategies and methods. Curriculum is a set of subjects and educational programs provided by an educational institution that contains a plan of lessons to be given to students in one period of education. The curriculum is not about how to apply textbooks, but also about how the direction of educational goals is expected to be achieved with the curriculum used. The term curriculum is used in the world of education. The learning carried out in the Movers school program refers to the profile of Pancasila students in order to strengthen the competence and character of students as one of the important components in the implementation of learning. the basic framework of the curriculum is the main foundation in developing the curriculum structure which is the reference for learning.